Análise de efluente e histologia da pele, fígado e rim de Pacus (Piaractus mesopotamicus) suplementados com cromo trivalente - Fujimoto, Rodrigo Yudi [UNESP]; da Cruz, Claudinei [UNESP]; de Moraes, Flavio Ruas [UNESP] (Inst Pesca, 2008)
The objective of this work was to evaluate the skin, liver and kidney histology of young pacus supplemented in diet with trivalent chromium and to evaluate the residue of chromium in water effluent. Randomised delineation by using factorial scheme 4x2, with four levels of chromium (0, 6, 12, 18 mg/L), two stocking densities (4 and 20 kg/m(3)), and four repetitions were used. Pacus with 100 g were used, for 90 days. An increase of the number of mucus cells and club cells in the epidermis of the pacus supplemented with 18 chromium mg/kg was observed in any stocking density. The same effect was observed in the liver, and in the highest density (20 kg/m(3)) the alterations already occurred at the level of 6 mg/kg with the inclusion of chromium, initially with congestion of sinusoids and getting worse at the level of 18 mg/kg with necrosis. The kidney didn't present visible morphologic alterations when supplemented and submitted to the stocking densities. The concentration of chromium in the effluent of pacus was 3.27 mu g/L in the higher level of supplementation (18 mg/L). In conclusion the level of 18 supplement mg/kg was not shown beneficial to the growth of pacus and the stocking density, due to the possible stress, accelerated the alteration histology process of tissues.
Analysis of effluents and histology of skin, liver and kidney the of pacus (Piaractus mesopotamicus) supplemented with trivalent chromium
Keywords: Supplement of chromium; effluents; histopathology; fish